Designing Macroscopic Surface Features Perceived as Soft During Finger Sliding - Qingyu Sun; Hongbo Wang; Shogo Okamoto (IEEE Access)
Humans evaluate material softness not only by pressing but also through stroking or rubbing motions. While previous studies have primarily focused on pressing to investigate compliance-related softness perception, the present study investigates softness perception during sliding, focusing on the “curved surface softness illusion,” in which slightly wavy surfaces feel softer than flat ones during fingertip sliding, despite being made of the same material. The objective of this study is to identify the surface features of sinusoidal surfaces that enhance the softness perceived in this illusion, using an optimal designing approach. A set of hard plastic specimens with varying wavelengths and amplitudes was manufactured based on a central composite design. Then, their perceived softness was evaluated in an experiment involving 32 participants. Results showed that perceived softness during sliding exhibited an inverted U-shaped function of both macroscopic sinusoidal wavelength and amplitude. A response surface method was then used to determine the design parameters that would maximize perceived softness. In a post-hoc experiment, the optimally designed specimen was rated as soft as the softest specimen in the initial experiment. The specimen judged as softest exhibited the surface wavelength of approximately 70 mm and amplitude of 0.40 mm. The findings of this study will enable the manipulation of softness perception through surface design, which will potentially be applied to consumer products. However, the mechanism of this perceptual phenomenon remains unknown and should be further investigated.